Implementation of the Balanced Scorecard in Performance Measurement of Waste Management in Mamuju Regency - Agus Erwin Ashari; Siti Rahmah; Nur Haidah; Fajar Akbar (Poltekkes Kemenkes Palu, 2025)
Waste remains a major environmental health issue in urban areas, requiring comprehensive management efforts that involve government, workers, and the community. In this regard, government accountability—both financial and non-financial—is essential. To ensure effective oversight, performance evaluation through the Balanced Scorecard (BSC) framework becomes crucial. In Mamuju Regency, waste management faces challenges, as only 5.55% of total waste is transported to final disposal sites. This study applies the BSC method to assess waste management performance in Mamuju, focusing on two perspectives: customer satisfaction and learning and growth. Using a quantitative descriptive design, data were collected from 50 residents who utilize household waste collection services and 100 employees directly engaged in operational waste services. Information was obtained through structured questionnaires, operational and financial reports, and supporting documentation from the relevant agency. The analysis covered attributes under the two BSC perspectives. Findings reveal that in the customer perspective—covering service quality, relationships, and institutional image—satisfaction reached the “satisfied” category, indicating good performance. Meanwhile, in the learning and growth perspective, which included employee competence, information system support, motivation, empowerment, and fairness, results showed “highly satisfactory” quality, placing performance in the “excellent” category. The study recommends that the Environmental and Sanitation Office of Mamuju Regency adopt the BSC systematically as a planning and evaluation tool. Local authorities should also design indicators suited to regional conditions, improve infrastructure, enforce the use of protective equipment, and encourage active community participation in waste management.